DETEKSI DINI SIMPTOM DEPRESI PADA REMAJA SMA NEGERI DI WILAYAH JAKARTA SELATAN - Idulfilastri, Rita Markus; Fransiska Angelika; Anastasya Dumyanti; Siti Bahiyah (Jurnal Bakti Masyarakat Indonesia, 2025)
Mental health is an important aspect of supporting the development of Indonesia's human resources,especially for the young population. Currently, there are many discussions about the behavior of schoolstudents that lead to depressive disorders. This PkM aims to detect depression using the SRED-7F instrument(Emotion Regulation Strategy with Simpton Depression-7Factor). The benefit for schools is to getrecommendations for student assessment reports and at the same time get a mapping of students classifiedas depressed. PkM activities began with an application for permission to obtain student data from theEducation Office Region I, South Jakarta. Data collection was carried out on January 21 and 22, 2025 anddata from 238 students were obtained. The results showed that 18% of students indicated depression, 49%indicated but could still be overcome, and the rest (37%) did not indicate symptoms of depression. It is alsoobtained how students overcome depression, namely using adaptive emotional regulation and simultaneouslysuppressing maladaptive emotional regulation (33%); more use of adaptive emotional regulation but has notbeen able to suppress maladaptive emotional regulation (27%); more use of maladaptive emotionalregulation but has not been able to use adaptive emotional regulation effectively (22%); not effectively usingadaptive and maladaptive emotional regulation (18%). Suggestions for schools to conduct depressionassessments for students on a regular basis including conducting training to improve the ability to developemotion regulation strategies. ABSTRAKKesehatan mental merupakan aspek penting mendukung pembangunan sumber daya manusia Indonesia, terutamabagi penduduk usia muda. Pada saat ini banyak pembahasan mengenai perilaku siswa sekolah yang mengarah padagangguan depresi. PkM ini bertujuan melakukan pendeteksian depresi menggunakan instrumen SRED-7F (StrategiRegulasi Emosi dengan Simpton Depresi-7Faktor). Manfaat bagi sekolah mendapat rekomendasi laporan asesmensiswa dan sekaligus mendapatkan pemetaan siswa tergolong depresi. Kegiatan PkM diawali dengan permohonan izinmendapatkan data siswa dari Suku Dinas Pendidikan wilayah I, Jakarta Selatan. Pengambilan data dilakukan pada21 dan 22 Januari 2025 dan diperoleh data dari 238 siswa. Hasil menunjukkan siswa terindikasi depresi sebesar18%, terindikasi tapi masih dapat diatasi sebesar 49% dan sisanya (37%) tidak terindikasi gejala depresi. Diperolehjuga cara siswa mengatasi depresi yaitu menggunakan regulasi emosi adaptif dan secara bersamaan menekanregulasi emosi maladaptif (33%); lebih banyak menggunakan regulasi emosi adapatif namun belum dapat menekanregulasi emosi maladaptif (27%); lebih banyak menggunakan regulasi emosi maladaptif tapi belum dapatmenggunakan regulasi emosi adaptif dengan efektif (22%); belum efektif menggunakan regulasi emosi adaptif danmaladaptif (18%). Saran bagi sekolah untuk melakukan asesmen deteksi dini depresi bagi siswa secara berkalatermasuk melakukan pelatihan untuk meningkat kemampuan menyusun strategi regulasi emosi.